Clinical Factors Predictive of COPD Diagnosis in a Community Hospital - Tongdee, Sukanya; Khamsai, Sittichai; Sawanyawisuth, Kittisak (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is an irreversible obstructive airway disease. Diagnosis can be made using a spirometry which may not be available in resource-limited setting or developing countries. AIM: This study aimed to evaluate if clinical factors can be predictive of COPD diagnosis. MATERIALS AND METHODS: This study was a retrospective cohort study conducted at community hospital. The inclusion criteria were adult patients who had clinical symptoms suggestive of COPD and had performed adequate pulmonary function tests. Patients were categorized into two groups by diagnosis of COPD. Clinical predictors of being COPD were executed by multivariate logistic regression analysis. RESULTS: There were 200 patients who met the study criteria. Of those, 136 patients (68.00%) had compatible pulmonary function test with COPD. There were eight factors in the final predictive model for being COPD (Table 1). Among these factors, three factors were independently associated with being COPD: Productive sputum, body mass index, and hyperinflation by chest X-ray. The hyperinflation by chest X-ray had highest adjusted odds ratio of 10.93 (95% CI 3.23, 36.96). CONCLUSIONS: Productive sputum, body mass index, and hyperinflation by chest X-ray were independent factors for COPD diagnosis. Physicians in resource-limited setting may use these clinical factors as diagnostic tool for COPD.